A Review of the Method of Using the Scalp Electric Field in EEG Analysis - Carvalhaes, Claudio; de Barros, J. Acacio (Cosmos and History: The Journal of Natural and Social Philosophy, 2015)
<!–[if gte mso 9]> <![endif]–> This paper reviews a recent method to study electroencephalogram (EEG) data involving a combination of the surface Laplacian and tangential electric field on the scalp. The method was applied to problems in EEG classification, where it was effective in improving results using data from a variety of experiments. The most relevant result was a 13.3% improvement on the average classification rate of a visual perception task involving nine different two-dimensional images. It also improved performance in language-comprehension and mental-imagery tasks. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>